(untitled) (Journal of Hama University, 2022)
The study was conducted on /18/ head of goats that were selected from several herds of goats, of the local breed, not pregnant, their ages ranged between/ 3-5/years, of both sexes, including males/4/heads, and females/14/heads. The degree of its obesity (BCS) ranged between /2-4 / degrees, The objective of this study was to investigate the gross and histo-pathological changes caused by the presence of soft foreign bodies in the rumen of goats, the research animals were placed within three Groups, each group included 6 heads, and the first group, which included healthy animals, was placed as a control to the experiment, and the second group had its animals infected with smooth foreign bodies, while the third group was also infected, but it was subjected to surgical treatment, there was found by gross examination of the second group’s animals carcasses, muscle atrophy and body fat loss. Congestion, erosions, papillae atrophy, with their loss in some places, were noted in the rumen mucosa, and a thinning of the rumen wall was found in some cases of research animals as well. Histopathological examination showed the presence of some inflammatory cells, atrophy, erosion and ulceration of the epithelial layer of papillae, and in some cases hyperkeratosis was seen, and prominent rete pegs take shapes Multiple epithelial islands of different thicknesses, in some cases, reaching the muscular layer with infiltration of mononuclear cells, lymphangiectasis vessels in the submucosal layer, and edema of the muscular and serous layers. Gross and histopathological examination of the rumen of animals of the third group treated with rumenatomy showed that the rumen mucosa appeared healthy and did not show any gross or histopathological changes, including the ruminal papillae, which seemed normal, except for two cases that had died due to peritonitis.